Uterine evacuation with prostaglandin E-1. - Cáceres, Eduardo (2015)
One hundred and thirteen patients treated with prostaglandine E-1 for uterine evacuation were studied at the Department of Obstetrics in Hospital "Edgardo Rebagliati Martins" of the Peruvian Social Security Institute, from January 1992 to December 1993. We looked for an alternative to oxitocin use for uterine evacuation because of medical reasons. Administration was oral, in occasions combined with vaginal route. Results were successful in 103 cases and unsuccessful in 10 (8,8%). Side effects were minimal. Oral administration, rare presentation of side effects and low percentage of failures, make it a practical choice in our daily practice. Its use shortens hospital stay, can be used by great multipara and previous cesarean section patients; it is a complement to surgical treatment.